2012
DOI: 10.1155/2012/912028
|View full text |Cite
|
Sign up to set email alerts
|

Topical Apigenin Alleviates Cutaneous Inflammation in Murine Models

Abstract: Herbal medicines have been used in preventing and treating skin disorders for centuries. It has been demonstrated that systemic administration of chrysanthemum extract exhibits anti-inflammatory properties. However, whether topical applications of apigenin, a constituent of chrysanthemum extract, influence cutaneous inflammation is still unclear. In the present study, we first tested whether topical applications of apigenin alleviate cutaneous inflammation in murine models of acute dermatitis. The murine model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 50 publications
0
32
0
2
Order By: Relevance
“…pH900 was used to measure skin surface pH. For barrier recovery, TEWL was measured at 0, 2 and 4 h after tape stripping (10‐fold increase in TEWL), and percentage barrier recovery was calculated as described earlier .…”
Section: Methodsmentioning
confidence: 99%
“…pH900 was used to measure skin surface pH. For barrier recovery, TEWL was measured at 0, 2 and 4 h after tape stripping (10‐fold increase in TEWL), and percentage barrier recovery was calculated as described earlier .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, botanical ingredients are increasingly being added to moisturizers, and some of these can be beneficial. For example, chamomile contains anti-inflammatory substances, such as apigenin, which can improve AD symptoms [6]. …”
Section: Moisturizers Do Not Equate With Barrier Repair Therapymentioning
confidence: 99%
“…In the recent past, several studies reported the mitigation of matrix metalloproteinases (MMPs) expression by apigenin in target cells, which is induced by several agents such as carcinogens, ultraviolet A (UVA 320–400 nm), phorbol myristate acetate (PMA), interleukin-1 beta (IL-1β) and tumor necrosis factor-alpha (TNF-α) [18]–[21]. Further, inhibitory action of apigenin or apigenin structural analogues against cutaneous inflammation and infection-induced inflammation is also demonstrated [22], [23]. However, no study claims the SVMP inhibitory efficacy of apigenin or derivatives having apigenin nucleus.…”
Section: Introductionmentioning
confidence: 99%